Conservative Decompression Management with Functional Appliance in Pediatric Plexiform Ameloblastoma - Kezia Rachellea Mustakim; Buyanbileg Sodnom-Ish; Mi-Young Eo; Hye-Jung Yoon; Hoon Myoung; Soung-Min Kim (Applied Sciences, 2021)
Ameloblastoma is an infiltrative benign neoplasm in the mandible or maxilla that is locally aggressive with rare metastasizing capacity. This lesion is the most common tumor of the odontogenic epithelium. However, its occurrence in children is low, representing only 10–15% of all reported ameloblastoma cases. In treating such benign neoplasms in pediatric patients, the preservation of vital structures such as the inferior alveolar nerve (IAN), deciduous teeth, tooth buds, and nerves with proper post-operative management to maintain normal mandibular growth is imperative. A five-year-old boy with painless swelling and displaced teeth in the right mandible was diagnosed with plexiform ameloblastoma. Instead of a radical approach, the patient was treated conservatively using decompression and routine irrigation along with long-term follow-up. Functional appliance treatment was provided using a Frankel appliance to preserve and induce normal growth of the jaw. After eight years, there was no recurrence of the ameloblastoma, and normal mandibular growth of the patient was observed. Pediatric plexiform ameloblastoma should be treated with a conservative approach considering the preservation of important anatomic structures and further mandibular growth. Moreover, functional appliance therapy should be considered as an integral part of treatment for pediatric ameloblastoma and other tumors in children to maintain and induce normal growth of the mandible.